Study of a western disturbance - SINGH , M.S; KUMAR, S. (MAUSAM, 1977)
The intensification of a western disturbance which moved from central Iran to northwest India from 11 to 13 February 1975 has been studied. It has been shown that the system intensified when a pre-existing surface low over central Iran was overtaken by a strong upper frontal layer from the west, It has also been shown how the strength of this upper frontal layer was maintained during the whole period.